Melembagakan indikator interaksi kependudukan, lingkungan hidup, dan pembangunan - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1993)
Abstract Increasing concern on the problem of carrying capacity in braod sense(natural, social, and environmental) wich support to the process of sustainable development has stimulated awareness on how important it is for the government and the community to maintain the development and environment in the perfect harmony. This paper discusses various attempt in developing needed by the government to monitor the performance of sustainable development. These effort are that the policy making should always be provided with exact, accurate, relevant andadvanced information on population qualities, environment,development strategies, and its related interaction Keywords: new policy indicators, stimulated awareness